Immunization With Bovine Herpesvirus-4-Based Vector Delivering PPRV-H Protein Protects Sheep From PPRV Challenge - Rodríguez-Martín, Daniel; Rojas, José Manuel; Macchi, Francesca; Franceschi, Valentina; Russo, Luca; Sevilla, Noemí; Donofrío, Gaetano; Martín, Verónica (Frontiers in Immunology, 2021)
The morbillivirus Peste des Petits Ruminants virus (PPRV) is the causal agent of a highly contagious disease that mostly affects sheep and goats and produces considerable losses in developing countries. Current PPRV control strategies rely on live attenuated vaccines, which are not ideal, as they cannot differentiate infected from vaccinated animals (DIVA). Recombinant vector-based vaccines expressing viral subunits can provide an alternative to conventional vaccines, as they can be easily paired with DIVA diagnostic tools. In the present work, we used the Bovine Herpesvirus-4-based vector (BoHV-4-A) to deliver PPRV hemagglutinin H antigen (BoHV-4-A-PPRV-H-ΔTK). Vaccination with BoHV-4-A-PPRV-H-ΔTK protected sheep from virulent PPRV challenge and prevented virus shedding. Protection correlated with anti-PPRV IgGs, neutralizing antibodies and IFN-γ producing cells induced by the vaccine. Detection of antibodies exclusively against H-PPRV in animal sera and not against other PPRV viral proteins such as F or N, could serve as a DIVA diagnostic test when using BoHV-4-A-PPRV-H-ΔTK as vaccine. Our data indicate that BoHV-4-A-PPRV-H-ΔTK could be a promising new approach for PPRV eradication programs.